Covid-19 automatic indoor safety control through mask, temperature and distance monitoring - Nehal, Md. Ashfak Haider; Islam, Tanjila; Jim, Abu Bakar Siddik; Fuad, Md. Tanvir (Brac University, 2023)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.